2018
DOI: 10.1177/0973801018800088
|View full text |Cite
|
Sign up to set email alerts
|

Risk-taking Channel of Monetary Policy: Evidence from Indian Banking

Abstract: Some recent articles have studied the link between the central bank’s monetary policy stance and the risk-taking behaviour of banks in the context of advanced economies. Loose monetary policy can encourage banks to reach for yield, which will increase their share of risky assets, and also induce them to use more short-term funding. We empirically examine the existence of this risk-taking channel of monetary policy transmission in India. We find that expansionary monetary policy may increase default risk partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This finding support the "search for yield" behaviour of banks (Rajan, 2005). Our result is also in line with the findings of Geng et al (2016) and Sarkar and Sensarma (2019) in the Indian context.…”
Section: Variablessupporting
confidence: 92%
“…This finding support the "search for yield" behaviour of banks (Rajan, 2005). Our result is also in line with the findings of Geng et al (2016) and Sarkar and Sensarma (2019) in the Indian context.…”
Section: Variablessupporting
confidence: 92%
“…This study uses the interbank overnight lending rate as the proxy of monetary policy. Regarding the demonstration of monetary policy changes, changes in interest rates (Djatche, 2019;Sarkar and Sensarma, 2019) or the gap between policy rates and the natural interest rate (Altunbas et al, 2014;Özşuca and Akbostancı, 2016) are utilized. Therefore, the research process will analyze these two settings separately to explore the similarities and differences in the results obtained.…”
Section: Methodsmentioning
confidence: 99%
“…At the micro level, it is mainly the borrower's factors that lead to a default on personal home mortgage loans. In the literature [24][25][26], by constructing a mortgage loan borrower default model, it was found that the borrower's job, income, family, health, and other aspects can affect the borrower's ability and willingness to repay the loan on time, causing the customer to default. The literature [27][28][29][30] considers credit risk as an important marketing variable for commercial banks' housing loan risk, which reflects the borrower's credit status and the risks associated with changes in income.…”
Section: Introductionmentioning
confidence: 99%